Alteraciones menstruales y nivel de estrés en adolescentes de la Federación Provincial de Loja - Aguirre López, Mercedes Janeth (2015)
The present study was conducted with the purpose to determine the menstrual abnormalities and the level of stress in adolescents of the “Federación Deportiva Provincial de Loja”. The study was of type quantitative , prospective, transversal; by applying the survey and stress tests in 147 lojanas adolescent sportswomen, was established 15 practicing sports more often of 2 to 4 hours of training which were volleyball, athletics, basketball, football, taekwondo, swimming, chess, wushu, karate do, boxing, skating career, gymnastics, weightlifting, judo and table tennis. It was determined that the main age of onset of menarche was between 12 to 13 years with a percentage of 53.06% and gynecological age between 1 and 3 years with 65.31%. Most teens maintain a balanced diet representing 61.22%. The body mass index was performed in base on the Z score of MSP, being determined normal weight with 74.83%, thinness in 17.69%, overweight 6.80% and extreme thinness with 0.68%. 80.95% of adolescent sportswomen have menstrual abnormalities, primary dysmenorrhea and oligomenorrhea being these the most frequent, predominating in the discipline of volleyball. The drug most commonly used for managing these disorders was the ibuprofen with 88.64%. The total population showed stress caused by the academic activities being most frequent low level with 68.03%. Therefore in this study evidenced evident high incidence of menstrual alterations and a low level of stress in adolescent sportswomen. Keywords : Menstrual disorders, stress, teenagers, sports.